Quality of Listening Assessment in Indonesian Book For SMA/SMK Class X Independent Curriculum - Desy Rufaidah; Ermawati Ermawati; Nanda Saputra; Hidayatun Nur; Sawrwiji Suwandi (Budapest International Research and Critics University, 2022)
To measure the achievement of learning objectives, it is necessary to conduct an assessment. This study aims to describe and explain the assessment, the suitability of the assessment with learning achievement, the readability of the listening assessment aspect in the Indonesian language textbook Class X Curriculum Merdeka: Smart and Intelligent in Indonesian Language and Literature. The data in this study will be qualitative and presented in words and sentences. Sources of data obtained from documents. Data was collected by document analysis. The data were analyzed using an interactive analysis model (Milles and Huberman). The results show that there are two aspects of listening assessment in the textbook, namely knowledge and skills. The dominant knowledge technique uses the assignment technique, then the writing technique, and verbal techniques are not used while the skills aspect only uses one technique, namely performance; the listening assessment in the CCBBI book already contains the learning outcomes of listening elements in accordance with the Independent Curriculum; and the readability of the textbook is in accordance with the PUEBI rules and is easy to understand. Based on the data, listening activities are carried out through text read by friends and videos, but the videos that are played in the text only contain visuals without sound, including text transcripts; not in accordance with the level of development of school age. listening activities are carried out through texts read by friends and videos, but videos that are played in text only contain visuals without sound, including text transcripts; not in accordance with the level of development of school age. listening activities are carried out through texts read by friends and videos, but videos that are played in text only contain visuals without sound, including text transcripts; not in accordance with the level of development of school age